Strategic Gestures in Bill McKibben's Climate Change Rhetoric - Bsumek, Peter K.; Schwarze, Steve; Peeples, Jennifer; Schneider, Jen (Frontiers in Communication, 2019)
Although Bill McKibben is widely recognized as one of the leading strategists of the US climate change movement, several observers identify significant limitations to his approach to climate advocacy and politics. These criticisms are based on his reliance upon “symbolic gestures,” such as campaigns to promote fossil fuel divestment and stop fossil fuel infrastructure construction. In this essay we reconsider McKibben’s work, drawing specifically on his speeches given from 2013-2016 in support of the fossil fuel divestment campaign and campaigns attempting to block the construction of fossil fuel infrastructure, in order to show how McKibben’s strategic orientation is grounded in a politics of gesture. His speeches provide a model for how to reconceive gestures and assemble them for political ends. Beyond the case of McKibben our analysis contributes the concept of strategic gestures to identify and theorize social movement interventions that have significant symbolic and material consequences.